Cultural Perspectives on Digital Scaffolding for Bilingual Education and Artificial Intelligence Engagement - Eljattari, Belkacem; Aboukhousa, Heba Ahmed; Saenz, Juan Jose; Boukraa, Driss (Journal of Cultural Analysis and Social Change, 2025)
While language instruction has always relied on scaffolding activities to help learners bridge the gap between basic receptive language and complex productive communication, the widespread adoption of generative AI models – coupled with the increasing demand for culturally responsive practice – has forced language learning professionals to reassess the efficacy of traditional scaffolding and explore ways of adapting their methods to fit this newly emerging paradigm. Although previous research has emphasized the benefits of AI in the classroom, this study examines its context through the lens of Arabic language instruction to non-native speakers. The study examines the benefits of AI-driven interactive learning tools first by framing the issue within the cultural and socio-political realities of language instruction within the Arab world. Through this context, the study examines continued efforts to enhance the competitiveness of Arabic in the global language market, hindered by logistical obstacles including limited institutional resources, fragmented educational policies, and tensions between Modern Standard Arabic and various Arabic dialects. Ultimately, this research argues that culturally sensitive digital scaffolding, coupled with AI, offers a sustainable path to advancing bilingual education and promoting intercultural understanding in an increasingly digitalized world.